Глибоке Озеро 2, Бондариха, Суботів: порівняння керамічних колекцій та деякі методичні пропозиції - Корохіна, А.В. (Археологія і давня історія України, 2021)
Робота присвячена апробації процедури структурування та порівняння комплексів археологічної кераміки. З метою пошуку закономірностей у
розподілі ознак матеріалу запропоновано застосування низки методів галузі «видобутку даних»
(data mining). Аналіз трьох колекцій фінального
періоду доби бронзи з Дніпро-Донецького лісостепового регіону (Глибоке Озеро 2, Бондариха, Суботів)
дозволив формалізувати їхні характеристики та
відмінності, що є підґрунтям для подальших досліджень. The paper provides an approbation of the procedure
of structuring and comparison of prehistoric ceramics
assemblages.
The proper tasking in the development of typology
of ancient pottery, from the «etic» position of analysis,
as the author argues, lies in the search of any non-accidental
patterns within artifacts assemblages, which
could be most likely regarded as a manifestation of a
«meaning». These ones could be revealed by analysis
of general morpho-functional classes (which enable to
investigate real categories, meaningful within past cultures)
and by applying the «data mining» techniques
(for finding out hidden patterns in arrays of continuous
numerical attributes). Statistical and multivariate
methods are also crucial in comparative analysis of
bulk arrays of artifacts.
To solve this tasks, it is proposed to apply: (1) measures
of assemblages diversity (richness, entropy, effective
number of species and evenness); (2) Pearson’s χ2
association test and correspondence analysis; (3) tests
on morphological homogeneity of assemblages, procedures
of separation of morphologically homogeneous
groups; (4) statistical characterization of morphological
groups; (5) comparison of morphological groups by
means of multivariate analysis of variances (MANOVA),
canonical discriminant analysis and regression
«decision trees».
The analysis of three assemblages of the Late Bronze
Age final stage from the Dnipro-Dinets’ rivers interflew
(Hlybore Ozero 2, Bondarykha and Subotiv) allowed to
formalize their characteristics and dissimilarities. This
creates a base for further researches, particularly in
the field of pre-historical reconstructions.
It has been revealed that the Subotiv’s ceramic assemblage
is typologically more diverse than assemblages
of Siverskiy Dinets’ region sites. On the other
hand, specificity of the Hlyboke Ozero 2 (site arose on
re-worked Timber-Grave Culture traditions) is evident
in quantitative parameters of morphological classes,
while the Bondarykha and the Subotiv are rather similar
in this measure.
Analysis of pot-like vessels indicates specificity of
Subotiv’s pottery production: local pots are distinctive
by relative neck height and heaps height. Comparison
of the Hlyboke Ozero 2 and the Bondarykha Culture assemblages
shows much the less dissimilarities between
these groups than between them and the Subotiv’s
one.
Pots from the Hlyboke Ozero 2 and the Subotiv show
slight morphological heterogeneity within the class.